Note per una teoria della metalessi - Concetta Maria Pagliuca (Status Quaestionis, 2024)
The essay aims to bring to the attention of the Italian context the most recent theoretical acquisitions on metalepsis. First, starting from the definition, an attempt was made to circumscribe the field by specifying what metalepsis is not. Then, in light of some of the main. contributions on the subject, an original interpretative map was proposed. The last paragraph is dedicated to ongoing research and possible future lines of investigation. The final bibliography aspires to be exhaustive and fruitful for further in-depth studies.